Pentingnya Evaluasi Hasil Belajar Di SMP - Alline Yoriana Putri, Jacinda; Abimanyu, Aditya (Jurnal Ilmiah Kanderang Tingang, 2024)
Learning evaluation at the Junior High School (SMP) level has an important role in ensuring the success of the learning process, forming a knowledge base, and developing students' critical thinking skills. Evaluation is used to assess learning outcomes, provide feedback, and assist students and teachers in identifying areas that need improvement. This study uses a literature review method by analyzing seven relevant articles from 2020-2024. The results of the study show that learning evaluation includes cognitive, affective, and psychomotor aspects, and is carried out through tests and non-tests. Effective evaluation helps teachers assess the success of the learning process, while for students, evaluation provides motivation to improve their achievements. However, some obstacles were found, such as difficulties in assessing attitudes and skills, which could be overcome through teacher training and improvement of evaluation instruments. With proper evaluation, it is hoped that the improvement of the quality of education in junior high schools can be achieved.